The impact of Palincsar and Brown Method of achievement for intermediate among Second Grade Students - Al-Janabi, Ammar Hadi; Flayeh, Ali El-aibi (Al-Adab Journal, 2018)
- There is no statistically significant difference at the level of significance (0.05) between the average scores of the students of the experimental group who study the material determined according to the Palincsar and Brown method and the grades of the control group students who study the same subject according to the usual method in achievement test The current research is determined by the average second-grade students in the middle and secondary schools of the General Directorate of Education in the governorate of Baghdad / Al-Rusafa for the academic year 2016-2017 and the three chapters of the content of the mathematics book for the second intermediate grade for the academic year 2016-2017 2015, To achieve the goal of the research, the researcher used the experimental design based on the two groups (experimental and control) equal partial control and the method of conducting the test tribal and remote, and chose the sample of students from the second grade intermediate in the middle of the new dawn to apply the research experience, The sample of the sample was (67) randomly distributed, randomly selected (B) to represent the experimental group, which would be studied according to the Bensak and Brown method. The number of students was 34, while the E randomly selected to represent the control group, The number of students was 33, and before the actual teaching was started, the students were statistically compensated by using the t-test for two independent samples and a square as in some variables, such as the age of months calculated and months of mathematics in the final exam for the first class of the academic year)2016- 2017), and previous knowledge in the article Aaziat, and matrix Ravn to measure intelligence, test scores and sports communication before the experiment, and did not appear there were statistically significant between the two groups in these variables differences. (154) behavioral objectives based on the content of the mathematics book scheduled for the second intermediate grade presented to a group of experts and specialists. After that, the researcher prepared model plans in teaching the subjects of the experiment in the style of Palincsar and Braun method for the experimental group students and in the traditional way for the students of the control group, presented to a group of experts and specialists. The researcher studied the two research groups himself, which lasted a full course.In order to achieve the objective of the research and its zero hypotheses, the preparation of two tools is required. The first is an achievement test prepared by the researcher in mathematics (the specific subject). It consists of (40) objective test subjects of the multiple choice type with four alternatives. The test paragraphs were distributed in the light of a test map at levels The three (recall, assimilation, application) of the classification of Bloom in the field of knowledge, and was verified the validity and stability and characteristics of cykometric by calculating the coefficient of difficulty and force discrimination and the effectiveness of alternatives to the wrong paragraphs (40) paragraph was characterized test entirely valid and reliable as well as the level of difficulty and discrimination of its paragraphs, which were all within the acceptable difficulty and discrimination term. Search results for:. students of the experimental group are more likely to have their peers in the control group in the achievement test. In the light of the results of the research, the researcher concluded that teaching according to the Bensakar and Brown method has a positive effect on increasing the achievement and developing the skills of mathematical communication among the students of the experimental group compared to the normal method of the control group. The researcher believes that training courses should be held for the mathematics teachers to train using the Bensak and Brown method. To train students to use the Bensk and Brown method in different subjects and different stages. The need to pay attention to the development of mathematical communication skills as objectives of teaching mathematics at all levels, Except for the current research aspects, the researcher suggests conducting other studies.